Black raspberries attenuate colonic adenoma development in ApcMin mice: Relationship to hypomethylation of promoters and gene bodies. Issue 3 (9th September 2020) - Huang, Yi‐Wen; Mo, Yue Yang; Echeveste, Carla Elena; Oshima, Kiyoko; Zhang, Jianying; Yearsley, Martha; Lin, Chien‐Wei; Yu, Jianhua; Liu, Pengyuan; Du, Ming; Sun, Chongde; Xiao, Jianbo; et al.
Abstract: Recent studies have suggested that in addition to promoter region, DNA methylation in intragenic and intergenic regions also changes during physiological processes and disease. The current study showed that feeding of black raspberries (BRBs) to Apc Min mice suppressed colon and intestinal tumors. MBDCap‐seq suggested that dietary BRBs hypomethylated promoter, intragenic, and intergenic regions. Annotation of those regions highlighted genes in pathways involved in immune regulation, inflammatory signaling, production of nitric oxide and reactive oxygen species, and progression of colorectal cancer. BRB phytochemicals (e.g., ellagic acid, anthocyanins, oligosaccharides) and their gut bacterial metabolites (e.g., urolithin, protocatechuic acid, short‐chain fatty acids) inhibited DNMT1 and DNMT3B activities in a cell‐free assay. Our results suggest that BRBs' hypomethylating activities result from the combined effects of multiple BRB phytochemicals and their gut bacterial metabolites. Because similar substances are found in many plant products, our results with BRBs might also apply to commonly consumed fruits and vegetables. Abstract : Black raspberries attenuate colonic adenoma through genomewide hypomethylation.